Karakter Psikopat dalam Film Ballerina Karya Lee Chung-Hyeon: Kajian Semiotik - Gusti, Nur Adilla Atitah; Setiawan, Heru; Wahyudin, Sapta Arif Nur (STKIP PGRI Ponorogo Press, 2026)
Literary works exist as a reflection of real life, drawing inspiration from the social environment of society. One of the results of literary works born from imagination and creativity is film. In this study, the researcher used the film Ballerina as their research object. The purpose of this study is to identify the characteristics of a psychopath in the character from the film. This research uses Charles Sanders Peirce's semiotic approach and descriptive qualitative methods. The data collection techniques in this study are listening, taking notes, and marking. As for data analysis, the researcher used data reduction, data presentation, and conclusion drawing techniques. It was therefore found that almost all the characters in the film Ballerina have psychopathic traits within them. This can be seen from the types 5 psychopathic characters found in the discussion of this study, including manipulative, sadistic behavior, lack of compassion, lack of guilt, and intelligence.